Socio-Economic Impact of the Emergence of Online Transportation in Indonesia: Opportunities and Challenges - Kusuma Dewi, Adinda Ariajati; Dani Fitria Brillianti (Kirana Publisher (KNPub), 2024)
In the current era, people can easily get pick-up and drop-off services via online transportation modes, this makes offline transport drivers such as angkot, bus and taxi drivers have their own challenges, on the other hand this also provides an opportunity for people to get pick-up services. pick up via online transportation mode. some people looking for work. By these developments, it is necessary to conduct research on the socio-economic impact of the emergence of online transportation to determine the opportunities and challenges for drivers regarding technological developments related to transportation. This study uses a survey method to determine the level of opportunities and challenges for offline and online drivers. The results obtained from the interviews were that there were negative and positive impacts experienced by drivers, both offline drivers and offline drivers had their own impacts. Online drivers get more opportunities and offline drivers get more challenges, because it is known that online transportation is more recommended and more chosen by the public as the main alternative.